ANALISIS MALE FEMINIS DAN KONTRA MALE FEMINIS NOVEL ANA CRITA ING PINGGIRE TEBON KARYA TULUS SETIYADI - Rifani, Fitria Ida; Sulaksono, Djoko; Fitriana, Tya Resta (Universitas Sebelas Maret, 2023)
This study is a descriptive qualitative research that’s aims to analysis male feminists and counter male feminists in the novel Ana Crita ing Pinggire Tebon by Tulus Setiyadi. Based on the content of the story that tells the life of the life of the character Wiyani is influenced by male characters, the novel is suitable to be studied with the study of feminism, espeially male feminists and counter male feminists. The data in the research are words, phrases, and sentences that are excerpts from the novel Ana Crita ing Pinggire Tebon. This research uses purposive sampling techniwue, data collection by means of document analysis. The validity test technique was carried out with theoritical triangulation and data source triangulation. The data analysis technique used was interactive analysis, with the sequence of data collection, data reduction, data presentation, and conclusion drawing. The results of the analysis in the study can be concluded that the caracters classified as male feminists are Pak Dali, Kicuk, Somad, Kumagrenks, and Kondektur. While those classified as counter male feminists are Sulinggo, Togut, Pak Bentu, Ko Bien, Sastropedo, and Ahmad.